The Human Resources Management and Artificial Intelligence - Abdulla, Nouf (Journal of Human Resource and Leadership, 2024)
Purpose: This paper aims to review the adoption of AI in supporting the HRM to enhance and boost their practices by utilizing artificial intelligence and the possibility of future integration of the human approach and AI approach. Methodology: This paper provides a qualitative approach based on the latest research, case studies, articles, and related literature. Finding: The paper describes the positive influence in the field of AI on the HRM practices/process. Unique Contribution to Theory, Practice and Policy: This paper provides an informative view of the positive influence of AI in enhancing the strategic HRM approach and organizational performance by adopting AI, and the implications/challenges of using AI in the HRM.